Development and evaluation of a patient passport to promote self-management in patients with heart diseases - Sabine Stamm-Balderjahn; Rebecca Faliniski; Susanne Rossek; Karla Spyra (BMC, 2019)
Abstract Background Patients with cardiovascular diseases (CVD) are treated over a long period of time by physicians and therapists from various institutions collaborating within a multidisciplinary team. Usually, medical records detailing the diagnoses and treatment regimens are long and extensive. Brief overviews of relevant diagnostic and treatment data in the form of a patient passport are currently missing in routine care for patients with CVD. This study aimed to develop and evaluate a patient passport (the Kardio-Pass) based on the needs of patients who had undergone cardiac rehabilitation, and of healthcare professionals. Methods A mixed method design was adopted consisting of an explorative qualitative phase followed by a quantitative evaluation phase. Interviews with patients and experts were conducted to develop the Kardio-Pass. CVD rehabilitees (N = 150) were asked to evaluate the passport using a semi-standardized written questionnaire. Results Patients and experts who were interviewed in the qualitative study phase considered the following passport contents to be particularly important: documentation of findings and diagnoses, cardiac diagnostics and intervention, medication plan, risk factors for heart disease, signs of a heart attack and what to do in an emergency. During the evaluation phase, 93 rehabilitees (response rate: 62%) completed the questionnaire. The Kardio-Pass achieved high overall approval: All respondents considered the information contained in the passport to be trustworthy. The professionalism and the design of the passport were rated very highly by 93 and 92% of participants, respectively. Use of the Kardio-Pass prompted 53% of participants to regularly attend follow-up appointments. The most common reasons for non-use were a lack of support from the attending doctor, failure by the patient to make entries in the passport, and loss of the passport. Conclusions By documenting the course of cardiac diseases, the patient passport pools all medical data-from diagnosis to treatment and aftercare-in a concise manner. Rehabilitees who used the cardiac passport rated it as a helpful tool for documenting follow-up data. However, with regard to this explorative study there is a need for further research, particularly on whether the patient passport can improve heart patient care.